FIGURE 1 in A new species of Sphaerodoridium Lützen, 1961 from Iceland (Polychaeta: Sphaerodoridae) - Moreira, Juan; Parapar, Julio (Zenodo, 2015)
FIGURE 1. Micrographs of Sphaerodoridium guerritai sp. nov. Holotype IINH 33095. A, full dorsal view; B, full ventral view; C, midbody segments, dorsal view; D, posterior end, dorsal view. Scale: A–B, 0.7 mm; C, 0.3 mm; D, 0.385 mm. Published as part of Moreira, Juan & Parapar, Julio, 2015, A new species of Sphaerodoridium Lützen, 1961 from Iceland (Polychaeta: Sphaerodoridae), pp. 91-105 in Zootaxa 3911 (1) on page 94, DOI:10.11646/zootaxa.3911.1.5, http://zenodo.org/record/236683